Germany : 2010 Article IV Consultation-Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Germany. (IMF Staff Country Reports; Country Report ;, 2010)
This 2010 Article IV Consultation highlights that the German economy is regaining the ground lost in the crisis. Policy support, restocking, and an uptick in global demand have lifted the economy from the recession. The authorities used the available fiscal space to implement countercyclical policy measures. Financial sector measures helped stabilize financial markets and mitigated systemic risk, but vulnerabilities remain. Executive Directors have welcomed the authorities' fiscal strategy that combines short-term support for the economy with a firm commitment to fiscal consolidation in the medium term.